Does Sustainable Development Promote Foreign Direct Investment in Pakistan? An ARDL Analysis - Sheikh, Muhammad Ramzan; Ali, Mehjabeen; Ahmad, Rashid; Bashir, Furrukh (iRASD Journal of Economics, 2022)
Foreign direct investment (FDI) has become a cornerstone for the public and private sectors, especially in developing countries as it can enhance social overhead capital and employment opportunities. This study examines the association between sustainable development and foreign direct investment in Pakistan over the period 1972-2021 by using the ARDL estimation technique. The study has used various variables i.e., foreign direct investment, sustainable development index, tax, exchange rate, credit, broad money and trade. The findings reveal that exchange rate, credit, broad money and trade are positively related to foreign direct investment while the tax has a negative effect on FDI. The study also points out that there is a long-run association between sustainable development and FDI. The study recommends that policymakers may enhance foreign direct investment through sustainable development, taxes reduction, financial development, exchange rate stability and trade in Pakistan.